Adobe Creative Suite 6 design tools Photoshop, Illustrator, and InDesign - Botello, Chris; Fisher, Ann (Writer on computers) (Illustrated series, 2013)
Presents each skill on two facing pages, providing detailed instructions on the left-hand page and large, full-color screenshots on the right page. In this book, the visual format helps students intuitively grasp the concepts and apply them to the classroom and workplace environment.